PERSONAL HYGIENE, WASHING EATING UTENSILS AND AMOUNT OF EATING UTENSILS BACTERIA AT THE FOOD SELLERS CENTER IN KAMPUNG SOLOR, KUPANG - ENNI ROSIDA SINAGA (JURNAL INFO KESEHATAN, 2013)
Introduction: Food and drink are human being’s daily need for living, growing and developing. To contribute well in human’s body, food and drink should meet nutrition, health, nature, and hygiene indicators. Therefore, food and drink treating management are needed by considering environmental sanitation, personal, and eating utensils hygiene. Based on assumption, in Indonesia 80% of food and drink related sicknesses were spread from the food. Diarrhea out break is frequently happened to people in Kupang as it was recorded from December 2008 to January 3th 2009; there were 284 victims with 3 deaths. Diarrhea can spread from food, drink, utensil, and waiters. Objective: To analyze the correlation of personal hygiene, washing eating utensils toward the amount of eating utensils bacteria in foods at the food sellers center in Kampung Solor, Kupang. Method: This research used observational analysis by using cross sectional technique. The population of this research was all 31 food sellers at food court sellers center. Subject of this research was 25 food sellers who used plates and glasses when serving food and drink. The independent variable in this research was personal hygiene, while the dependent variable was the amount of eating utensils bacteria. The data were collected by using check list from observation and microbiology check conducted to plates and glasses in laboratory. The data were processed and analyzed by using Chi Square statistical test with univariate, bivariate (OR, CC) analysis at α = 0.05. Analysis and Result: Bivariate analysis showed that there were significant correlation in washing eating utensils 0.041 at OR 7.700 point. The significance relationship of washing eating equipments toward the amount of eating equipments bacteria were presented at C 0.025 for washing eating utensils. Conclusion: Washing eating utensils properly showed significant relationship toward the amount of eating utensils bacteria. Waste solid, waste disposal, and personal hygiene showed no significant correlation toward the amount of eating utensils bacteria.